Pengaruh Temperatur dan Lama Thawing terhadap Kualitas Spermatozoa Sapi dalam Penyimpanan Straw Beku - S Utomo; E Boquifai (Universitas Sebelas Maret (UNS), 2010)
This research was conducted to investigate the effect of temperature and duration ofthawing frozen semen in ministraw on quality sperm. Seventy five ministraws frozen semen of Simmental breed were thawing by water with temperature 5, 26 and 37 °C, with duration of 5, 10, 15, 20 and 30 second. The quality sperm post thawing was measured based on pH and motility. The design of this research was completely randomized design with factorial clasification 3 x 5. The result showed that the motility of sperm was thawing 37°C better than the other temperature. The quality of sperm was no affected by temperature and duration of thawing. It could be concludedthat thawing of frozen semen will have better done at 37°C with duration of 15 second.Key words : Thawing, sperm, ministraw, frozen semen.